Cyberterrorist Messages and Their Effects on Targets: A Qualitative Analysis. - Minei, Elizabeth; Matusitz, Jonathan (Journal of Human Behavior in the Social Environment, 2011)
This study provides a semiotic perspective on cyberterrorism and its opportunity to cause maximal damage while using terrorist propaganda. Data were gathered via in-depth qualitative interviewing. Information was obtained from 10 participants, all of them being law enforcement (LE) agents (e.g., from a U.S. federal agency such as the FBI) or cyber forensics experts. From the participants' narratives, five themes emerged: (1) acknowledgement of the existence of cyberterrorism, (2) postmodern propaganda and publicity, (3) detrimental effects on targets, (4) media implications, and (5) communicative messages.